Gender Intersectionality Representation in Boule de Suif by Guy de Maupassant - Savitri, Intan Dewi; Khotimah, Siti Khusnul; Apriyanti, Komang Dyah; Wicaksana, Dewa Maulana (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
Boule de Suif is considered one of the best short stories written by Guy de Maupassant. This study is based on a feminist perspective applying a narrative approach to provide an overview of the intersectionality of gender in Guy de Maupassant's narrative work, The Boule de Suif. Specifically, the narrative model was chosen as an approach that focuses on the individual stories of the characters within the work. Narrative identification is important for unraveling issues of gender intersectionality that arise in unequal phenomena. From the process of analysis, it is clear that the character Boule de Suif experiences the phenomenon of intersectionality of gender in the categories of gender, social class and identity in a situation of mutual support, trying to protect themselves from a violent war.